PEMBELAJARAN NAHWU DENGAN METODE DEDUKTIF DAN INDUKTIF - Supardi, Adi; Gumilar, Agung; Abdurohman, Rizki (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2022)
This article aims to describe Nahwu learning through deductive and inductive methods. Nahwu learning in Indonesia has been going on for a long time, massive and dynamic. So that innovations from Arabic language experts continue to be carried out in an effort to answer the needs of the community. The Nahwu learning method is divided into two groups, namely the al-qiyâsiyyah method (deductive/general to specific) and the al-istiqrâ'iyyah method (inductive/specific to general). This study uses a qualitative type of research through a descriptive analysis approach to library research. The data comes from classical literature, namely syarh matan Jurūmiyyah and Mulakhos Qowâid Lughoh Arobiyyah, and modern literature, namely An-Nahwul Wâdih and al-muyassar fī ilmi An-Nahwi. The technique of collecting data is through content analysis from available literature, then it is analyzed and described in its entirety. By definition, the deductive method is Nahwu learning which is centered on rules to examples. This deductive method strategy uses rules that are concise and easy to memorize, strengthens memorization with verse verses, as well as rules that are often repeated and then inspired by the use of word examples. The innovation in this deductive method uses the strengthening of the memorization of the rules through the verses of the Nahwu rules that are sung. By implication, this deductive method is considered right on target if it is used by adult students or who are fluent in reading and speaking Arabic as theoretical reinforcement. Meanwhile, the inductive method by definition means mastery of sentence examples rather than rules, students are encouraged to master practical and applicable examples so that they are able to practice them in everyday conversation. Strategically, this method is by making an example of a practical sentence by the teacher and then followed by students, then after memorizing the example, students are expected to be able to make other examples, after being able to make examples, the teacher explains the rules as reinforcement and theory affirmations. Innovation that can be done by training students to make simple sentences with everyday themes. The implications of the method are considered highly for beginners who are just learning Arabic, they are prioritized to be able to make examples and practice them rather than theory.